Organoprotective Eﬀects of Extracorporeal Membrane Oxygenation and Intra-Aortic Balloon Pump in High-Risk Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome - R. A. Kornelyuk; D. L. Shukevich; I. E. Vereshchagin; V. I. Ganyukov (Общая реаниматология)
Purpose of the study: to evaluate the organoprotective eﬀects of veno-arterial extracorporeal membrane oxygenation and intra-aortic balloon pump during high-risk percutaneous coronary intervention in acute coronary syndrome.Materials and methods. Patients required mechanical circulatory support (n=51) were divided into two study groups: patients who received mechanical circulatory support by veno-arterial extracorporeal membrane oxygenation (ECMO) (Group 1, n=29) during high-risk percutaneous coronary intervention, and Group 2 patients who received mechanical circulatory support by intra-aortic balloon pump (IABP) during high-risk percutaneous coronary intervention (Group 2, n=22). The dynamics of instrumental parameters and laboratory markers of organ damage were evaluated by electrocardiography, echocardiography, determining troponin I, creatine phosphokinases and creatinine levels, NGAL, venous blood saturation to compare the organoprotective properties of mechanical circulation support in the intra- and postoperative period.Results. The following values of the parameters were found the next day after the intervention: troponin I — 0.18 (0.1; 2.3) ng/ml in the ECMO group and 1.64 (0.92; 2.36) ng/ml in the IABP group (P=0.045); serum NGAL —139.4 (88.1; 166.7) ng/ml in the ECMO group and 212.3 (102; 279) in the IABP group (P=0.027); renal dysfunction (stages R, I, F according to RIFLE) — 2 (6.8%) observations in the ECMO group and 7 (31.8%) in the IABP group (P=0.021); multiple organ failure (2 or more points according to SOFA) — 3 (10.3%) cases in the ECMO group and 12 (54.5%) in the IABP group (P=0.001).Conclusion. Veno-arterial ECMO in comparison with IABP has a more pronounced organoprotective eﬀect by achieving better hemodynamic stability, which, in turn, prevents hypoxia and the subsequent development of organ dysfunction. In addition, in conditions of veno-arterial ECMO, better completeness and quality of revascularization is ensured, and hospital mortality is also reduced.